Degradable white and near-infrared dual-mode luminescent nanocrystal, preparation method and application thereof

By preparing rare earth nanocrystals with core-shell-shell structures, the problem of difficulty in degrading rare earth up-converted nanocrystals in the body is solved, biodegradability and efficient near-infrared fluorescence emission are achieved, and the potential of its bioimaging and therapeutic applications is enhanced. .

CN117186889BInactive Publication Date: 2024-12-27NORTHEAST FORESTRY UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311119553.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-01
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing rare earth up-converted nanocrystals are difficult to degrade in biological organisms, resulting in accumulation in volume and affecting their clinical application.

Method used

The oxides of rare earth metals ytterbium, erbium, cerium and thulium were reacted with trifluoroacetic acid solution, and the core-shell-shell structure Na3ZrF7:Yb,Er,Ce@CaF2:Yb,Tm were prepared by high-temperature solvothermal method and coating method. ,Zr@CaF2:Zr nanocrystals, have white and near infrared two-zone dual-mode luminescence properties, and achieve biodegradation with the help of CaF2 shell.

Benefits of technology

The biodegradability of nanocrystals and efficient near-infrared fluorescence emission are achieved, enhancing its application potential in bioimaging and treatment, while avoiding the risk of accumulation in volume.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117186889B_ABST
    Figure CN117186889B_ABST
Patent Text Reader

Abstract

The invention provides a white and near-infrared dual-mode luminescent degradable nanocrystal, a preparation method and an application thereof. The trifluoroacetates of rare earth metals ytterbium, erbium and cerium and zirconium acetate solid are used as raw materials, and a high-temperature solvent thermal method is adopted to prepare core nanocrystals Na3ZrF7:Yb,Er,Ce; then Ca(CF3COO)2, zirconium acetate, and trifluoroacetates of rare earth metals ytterbium and thulium are added, and a coating method is adopted to prepare core-shell nanocrystals Na3ZrF7:Yb,Er,Ce@CaF2:Yb,Tm,Zr; finally, Ca(CF3COO)2 and zirconium acetate are added, and a coating method is adopted again to prepare nanocrystals Na3ZrF7:Yb,Er,Ce@CaF2:Yb,Tm,Zr@CaF2:Zr with a core-shell-shell structure. The preparation method has a simple and easy synthetic route, uniform particle size distribution, high product purity, and is green and environmentally friendly. By doping with different rare earth elements and constructing a core-shell structure, the nanocrystals are given strong white and near-infrared fluorescence. The near-infrared fluorescence makes it a potential optical imaging contrast agent, while the white light emission makes the prepared nanocrystals usable as a nano energy "converter" for light-triggered therapy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of nanocrystal preparation technology, and in particular to a degradable white and near-infrared dual-mode luminescent nanocrystal, a preparation method and application thereof. Background Art

[0002] The application of lanthanide-doped inorganic luminescent nanoparticles (LDNPs) as deep tissue penetrating fluorescent diagnostic and therapeutic agents has attracted many researchers in the past few years. These lanthanide-doped inorganic luminescent nanoparticles (LDNPs) utilize certain specific lanthanide ions (such as Er 3+ )'s outstanding nonlinear up-conversion luminescence (UCL) and / or near-infrared (NIR) down-conversion luminescence (DSL) realizes near-infrared excitation and fluorescence signal detection in deep parts of the living body, with less damage to the organism and less background interference, bringing great prospects for biomedical imaging.

[0003] Fluorescence imaging in the second near-infrared window (NIR-II, 1000−1700 nm) has been greatly explored for its unprecedented tissue penetration and spatial resolution compared to conventional near-infrared (NIR-I, 700−900 nm) fluorescence imaging, due to minimal photon absorption and scattering, and negligible tissue autofluorescence. As an excellent candidate for fluorescence imaging in the NIR-II window, rare earth doped down-shifted nanoparticles (DSNPs) have excellent optical properties such as a clear emission band, a large Stokes shift, no photobleaching, and a long fluorescence lifetime. In fact, some progress has been made in NIR-II bioimaging due to the construction of NIR-II emitting LDNPs. For example, some literature has reported the use of Yb / Ce / Er or Ce / Er co-doped nanoparticles for NIR-II biosensing or bioimaging. However, the high doping content of Ce will inevitably cause matrix lattice defects and reduce the total emission intensity. And because single-modality imaging technology has inherent shortcomings and cannot provide comprehensive lesion information, it is difficult to obtain accurate disease diagnosis. Therefore, for rare earth luminescent nanocrystals, in order to achieve efficient cancer diagnosis and treatment and other related functions, it is of great significance to simultaneously endow them with up-conversion and down-conversion near-infrared dual-mode luminescence properties.

[0004] In terms of biological applications, researchers hope that rare earth upconversion nanocrystals can be degraded into harmless products that are easy to remove after they have completed their diagnostic and therapeutic functions in the body, and then be harmlessly excreted from the body within a reasonable time. However, the rare earth upconversion nanocrystals currently developed are characterized by "rigidity" and physiological inertness, which makes them unable to degrade in the body, especially in a relatively mild physiological microenvironment. Even if water-soluble functional ligands are coated on the surface, such rare earth upconversion nanocrystals will still accumulate in important organs, causing damage to the organism, such as liver and spleen necrosis. Although rare earth upconversion nanocrystals have great potential for a variety of biological applications, this dilemma has become one of the biggest obstacles to their clinical application.

[0005] In summary, no scheme or path has been reported for preparing rare earth fluoride nanocrystals with strong white and near-infrared dual-mode luminescence and biodegradability using near-infrared light as the excitation light source. Summary of the invention

[0006] The present application provides a degradable white and near-infrared dual-mode luminescent nanocrystal, a preparation method and application thereof to solve the problems of the prior art.

[0007] In a first aspect, the present application provides a method for preparing a white and near-infrared dual-mode luminescent degradable nanocrystal, comprising the following steps:

[0008] S1, reacting oxides of rare earth metals ytterbium, erbium, cerium and thulium with a trifluoroacetic acid solution to obtain trifluoroacetates of rare earth metals ytterbium, erbium, cerium and thulium;

[0009] S2, using the trifluoroacetates of rare earth metals ytterbium, erbium and cerium and zirconium acetate solids prepared in step S1 as raw materials, and adopting a high temperature solvothermal method to prepare core nanocrystals Na3ZrF7:Yb,Er,Ce;

[0010] S3, adding trifluoroacetate of Ca(CF3COO)2, zirconium acetate, rare earth metals ytterbium and thulium to core nanocrystals Na3ZrF7:Yb,Er,Ce, and preparing core-shell nanocrystals Na3ZrF7:Yb,Er,Ce@CaF2:Yb,Tm,Zr by coating method;

[0011] S4, Ca(CF3COO)2 and zirconium acetate were added to the core-shell nanocrystals Na3ZrF7:Yb,Er,Ce@CaF2:Yb,Tm,Zr, and the core-shell-shell nanocrystals Na3ZrF7:Yb,Er,Ce@CaF2:Yb,Tm,Zr@CaF2:Zr were prepared by the coating method again.

[0012] Furthermore, step S1 specifically includes:

[0013] At room temperature, 10 mmol to 30 mmol of oxides of rare earth metals ytterbium, erbium, cerium and thulium and 60 mmol to 180 mmol of trifluoroacetic acid are respectively taken in a container and mixed evenly, the mixed solution is slowly heated to 80°C under stirring, 10 mL to 20 mL of distilled water is added and the reaction is continued for 0.5 h to 1 h, then the solution is cooled and filtered to obtain a rare earth metal trifluoroacetate solution, and the solution is further heated and evaporated at 60°C to 100°C until trifluoroacetate compound crystals are precipitated, and then dried to obtain a solid powder which is the trifluoroacetate of the corresponding rare earth element.

[0014] Furthermore, between step S1 and step S2, the following steps are also included:

[0015] A zirconium acetate solution with a concentration of 15% to 16% is slowly heated until zirconium acetate crystals precipitate on the surface of the solution, and then transferred to an oven at 60°C to 80°C for drying to obtain solid zirconium acetate powder.

[0016] Further, step S2 mainly includes:

[0017] Weigh 75% zirconium acetate, 20% ytterbium trifluoroacetate, 2% erbium trifluoroacetate and 3% cerium trifluoroacetate in molar fractions into a reaction flask, add oleic acid and octadecene in a volume ratio of 1:2 to form solution A; heat the solution A to 120°C to 140°C under vacuum, turn off the vacuum device when no bubbles are generated, pass nitrogen for 20min to 40min, then heat to 150°C to 160°C, keep for 20min to 40min, and then cool to 40~50°C for use; add 10~15mL of solution A to a flask ... A methanol solution containing 2 to 4 times the amount of sodium hydroxide and 3 to 6 times the amount of ammonium fluoride as the amount of a rare earth trifluoroacetate precursor is added to the solution A after the reaction and the stirring is continued for 30 to 45 minutes. The reaction system is then heated to 120 to 140° C. under stirring and vacuuming. When no bubbles are generated, the vacuum device is closed and nitrogen is passed through for 20 to 40 minutes. The temperature is then raised to 240 to 260° C. again and maintained for 40 to 60 minutes. The reaction system is then naturally cooled to room temperature to obtain core nanocrystals Na3ZrF7:Yb, Er, Ce.

[0018] Further, step S3 mainly includes:

[0019] Calculated by the molar fraction, 79.5% Ca(CF3COO)2, 20% ytterbium trifluoroacetate, 0.5% thulium trifluoroacetate and 1% zirconium acetate were directly added to a reaction flask containing core nanocrystals Na3ZrF7:Yb,Er,Ce, and heated to 120-140°C under stirring and vacuum. When no bubbles were generated, the vacuum device was turned off, nitrogen was passed through for 0.5-1h, then the temperature was raised to 250-270°C for reaction for 1-1.5h, and then cooled to room temperature to obtain core-shell nanocrystals Na3ZrF7:Yb,Er,Ce@CaF2:Yb,Tm,Zr.

[0020] Furthermore, the ratio of the amount of the core nanocrystal to the sum of the amounts of Ca(CF3COO)2, ytterbium trifluoroacetate, thulium trifluoroacetate and zirconium acetate is 1:2.

[0021] Further, step S4 mainly includes:

[0022] According to the molar fraction, 97% Ca(CF3COO)2 and 3% zirconium acetate are directly added to a reaction flask containing core-shell nanocrystals Na3ZrF7:Yb,Er,Ce@CaF2:Yb,Tm; the mixture is heated to 120°C ~140°C under stirring and vacuuming, and when no bubbles are generated in the reaction flask, the vacuuming device is turned off, nitrogen is passed through and maintained for 0.5~1h, the temperature is raised to 250~270°C again, the reaction is carried out for 1~1.5h, and the mixture is naturally cooled to room temperature to obtain core-shell-shell nanocrystals Na3ZrF7:Yb,Er,Ce@CaF2:Yb,Tm,Zr@CaF2:Zr.

[0023] Furthermore, the amount of the core-shell nanocrystals is the same as the sum of the amounts of Ca(CF3COO)2 and zirconium acetate.

[0024] In the second aspect, the present invention provides a core-shell-shell nanocrystal prepared by the preparation method of white and near-infrared dual-mode luminescent degradable nanocrystals described in the first aspect, and the chemical expression is: Na3ZrF7:Yb,Er,Ce@CaF2:Yb,Tm,Zr@CaF2:Zr.

[0025] In a third aspect, the present invention provides the use of the white and near-infrared dual-mode luminescent degradable nanocrystals provided in the second aspect in the preparation of biological imaging probes or drug carriers.

[0026] The above technical solution provided by the present invention has the following advantages compared with the prior art:

[0027] The invention provides a white and near-infrared two-zone dual-mode luminescent degradable nanocrystal, a preparation method and an application thereof. The nanocrystal Na3ZrF7:Yb, Er, Ce@CaF2:Yb, Tm, Zr@CaF2:Zr is prepared by a high-temperature solvent thermal method and an epitaxial growth method. Ytterbium ions in the core are used as a sensitizer to capture 980 nm photons. Due to the unique cross-relaxation effect between cerium and erbium, after ytterbium transfers energy to the activator erbium ions, photons on the near-infrared two-zone light energy level of erbium are rapidly accumulated, while photons on the red and green light energy levels of erbium are sharply reduced, and the near-infrared two-zone emission is strongest when the doping concentration of cerium is 3%. In the invention, the core size is small, and the core with a small size is conducive to increasing the probability of occurrence of such cross-relaxation.

[0028] The present invention doped thulium ions with a concentration of 0.5% in the first CaF2 shell layer, giving the nanocrystals blue-violet upconversion, and due to the presence of red and green upconversion fluorescence of erbium ions, the overall luminescence of the nanocrystals is white. The outermost coated CaF2 shell layer can eliminate the fluorescence quenching of thulium ions and greatly improve the intensity of upconversion white luminescence.

[0029] The preparation method of the present invention has a simple and easy synthetic route, uniform particle size distribution, high product purity, and is green and environmentally friendly. By doping with different rare earth elements and constructing a core-shell structure, the nanocrystals are given strong white and near-infrared fluorescence. The near-infrared fluorescence makes it a potential optical imaging contrast agent, while the white light emission makes the prepared nanocrystals usable as a nano energy "converter" for light-triggered therapy.

[0030] In addition, the biodegradability of the product of the present invention enables the rare earth upconversion nanocrystals to biodegrade into harmless products after fulfilling their diagnostic and therapeutic functions in the body, and can be metabolized out of the body, while the CaF2 shell has a regulating effect on the degradation rate of the nanocrystals. Therefore, the nanocrystals can be used as a potential integrated diagnostic and therapeutic nano-platform. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0032] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0033] Figure 1 is a transmission electron microscope image of the core nanocrystal prepared by the high temperature solvothermal method in Example 1;

[0034] Figure 2 is a transmission electron microscope image of the core-shell-shell nanocrystal prepared by continuous coating using the epitaxial growth method in Example 1;

[0035] Figure 3 The X-ray diffraction patterns of the core nanocrystals and the core-shell-shell nanocrystals obtained in Example 1 and the standard card of tetragonal phase Na3ZrF7;

[0036] Figure 4 is a transmission electron microscopy image of the core-shell-shell nanocrystals obtained in Example 1 after being degraded in PBS (pH=5.5) for twelve hours;

[0037] Figure 5 is an up-conversion emission spectrum of the core nanocrystal and the core-shell-shell nanocrystal in Example 1 excited by 980nm laser;

[0038] Figure 6 This is an upconversion luminescence photograph of the core-shell-shell nanocrystal in Example 1 excited by 980nm laser;

[0039] Figure 7 It is a down-conversion emission spectrum diagram of the core nanocrystal and the core-shell-shell nanocrystal in Example 1 using 980nm laser excitation.

[0040] Figure 8 This is the color coordinate diagram corresponding to the up-conversion emission spectrum of the core-shell-shell structure nanocrystals prepared in Example 1. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0042] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0043] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present application specification, the terms "including", "comprising", etc. refer to "including but not limited to". In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of the associated objects, indicating that there may be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A, B can be singular or plural. In this article, "at least one" refers to one or more, and "plural" refers to two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items (individuals) or plural items (individuals). For example, "at least one of a, b, or c", or "at least one of a, b and c", can both mean: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b, c can be single or plural, respectively.

[0044] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0045] In a first aspect, the present application provides a method for preparing a white and near-infrared dual-mode luminescent degradable nanocrystal, comprising the following steps:

[0046] S1, reacting oxides of rare earth metals ytterbium, erbium, cerium and thulium with a trifluoroacetic acid solution to obtain trifluoroacetates of rare earth metals ytterbium, erbium, cerium and thulium;

[0047] S2, using the trifluoroacetates of rare earth metals ytterbium, erbium and cerium and zirconium acetate solids prepared in step S1 as raw materials, and adopting a high temperature solvothermal method to prepare core nanocrystals Na3ZrF7:Yb,Er,Ce;

[0048] S3, adding trifluoroacetate of Ca(CF3COO)2, zirconium acetate, rare earth metals ytterbium and thulium to core nanocrystals Na3ZrF7:Yb,Er,Ce, and preparing core-shell nanocrystals Na3ZrF7:Yb,Er,Ce@CaF2:Yb,Tm,Zr by coating method;

[0049] S4, Ca(CF3COO)2 and zirconium acetate were added to the core-shell nanocrystals Na3ZrF7:Yb,Er,Ce@CaF2:Yb,Tm,Zr, and the core-shell-shell nanocrystals Na3ZrF7:Yb,Er,Ce@CaF2:Yb,Tm,Zr@CaF2:Zr were prepared by the coating method again.

[0050] Furthermore, step S1 specifically includes:

[0051] At room temperature, 10 mmol to 30 mmol of oxides of rare earth metals ytterbium, erbium, cerium and thulium and 60 mmol to 180 mmol of trifluoroacetic acid are respectively taken in a container and mixed evenly, the mixed solution is slowly heated to 80°C under stirring, 10 mL to 20 mL of distilled water is added and the reaction is continued for 0.5 h to 1 h, then the solution is cooled and filtered to obtain a rare earth metal trifluoroacetate solution, and the solution is further heated and evaporated at 60°C to 100°C until trifluoroacetate compound crystals are precipitated, and then dried to obtain a solid powder which is the trifluoroacetate of the corresponding rare earth element.

[0052] In some implementations, the method further includes between step S1 and step S2:

[0053] A zirconium acetate solution with a concentration of 15% to 16% is slowly heated until zirconium acetate crystals precipitate on the surface of the solution, and then transferred to an oven at 60°C to 80°C for drying to obtain solid zirconium acetate powder.

[0054] In some implementations, step S2 mainly includes:

[0055] Weigh 75% zirconium acetate, 20% ytterbium trifluoroacetate, 2% erbium trifluoroacetate and 3% cerium trifluoroacetate in molar fractions into a reaction flask, add oleic acid and octadecene in a volume ratio of 1:2 to form solution A; heat the solution A to 120°C to 140°C under vacuum, turn off the vacuum device when no bubbles are generated, pass nitrogen for 20min to 40min, then heat to 150°C to 160°C, keep for 20min to 40min, and then cool to 40~50°C for use; add 10~15mL of solution A to a flask ... A methanol solution containing 2 to 4 times the amount of sodium hydroxide and 3 to 6 times the amount of ammonium fluoride as the amount of a rare earth trifluoroacetate precursor is added to the solution A after the reaction and the stirring is continued for 30 to 45 minutes. The reaction system is then heated to 120 to 140° C. under stirring and vacuuming. When no bubbles are generated, the vacuum device is closed and nitrogen is passed through for 20 to 40 minutes. The temperature is then raised to 240 to 260° C. again and maintained for 40 to 60 minutes. The reaction system is then naturally cooled to room temperature to obtain core nanocrystals Na3ZrF7:Yb, Er, Ce.

[0056] In some implementations, step S3 mainly includes:

[0057] Calculated by the molar fraction, 79.5% Ca(CF3COO)2, 20% ytterbium trifluoroacetate, 0.5% thulium trifluoroacetate and 1% zirconium acetate were directly added to a reaction flask containing core nanocrystals Na3ZrF7:Yb,Er,Ce, and heated to 120-140°C under stirring and vacuum. When no bubbles were generated, the vacuum device was turned off, nitrogen was passed through for 0.5-1h, then the temperature was raised to 250-270°C for reaction for 1-1.5h, and then cooled to room temperature to obtain core-shell nanocrystals Na3ZrF7:Yb,Er,Ce@CaF2:Yb,Tm,Zr.

[0058] In some embodiments, the ratio of the amount of the core nanocrystal substance to the sum of the amounts of Ca(CF3COO)2, ytterbium trifluoroacetate, thulium trifluoroacetate, and zirconium acetate substances is 1:2.

[0059] In some implementations, step S4 mainly includes:

[0060] According to the molar fraction, 97% Ca(CF3COO)2 and 3% zirconium acetate are directly added to a reaction flask containing core-shell nanocrystals Na3ZrF7:Yb,Er,Ce@CaF2:Yb,Tm; the mixture is heated to 120°C ~140°C under stirring and vacuuming, and when no bubbles are generated in the reaction flask, the vacuuming device is turned off, nitrogen is passed through and maintained for 0.5~1h, the temperature is raised to 250~270°C again, the reaction is carried out for 1~1.5h, and the mixture is naturally cooled to room temperature to obtain core-shell-shell nanocrystals Na3ZrF7:Yb,Er,Ce@CaF2:Yb,Tm,Zr@CaF2:Zr.

[0061] In some embodiments, the amount of the core-shell nanocrystals is the same as the sum of the amounts of Ca(CF3COO)2 and zirconium acetate.

[0062] In the second aspect, the present invention provides a core-shell-shell nanocrystal prepared by the preparation method of white and near-infrared dual-mode luminescent degradable nanocrystals described in the first aspect, and the chemical expression is: Na3ZrF7:Yb,Er,Ce@CaF2:Yb,Tm,Zr@CaF2:Zr.

[0063] In a third aspect, the present invention provides the use of the white and near-infrared dual-mode luminescent degradable nanocrystals provided in the second aspect in the preparation of biological imaging probes or drug carriers.

[0064] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.

[0065] Embodiment 1:

[0066] This embodiment provides a white and near-infrared dual-mode luminescent degradable nanocrystal, and the preparation method includes the following steps:

[0067] (1) Synthesizing trifluoroacetates and zirconium acetates of rare earth metal elements ytterbium, erbium, cerium and thulium respectively: at room temperature, take 10 mmol of oxides of rare earth metals ytterbium, erbium, cerium and thulium and 60 mmol of trifluoroacetic acid respectively and mix them evenly in a container, slowly heat the mixed solution to 80°C under stirring, add 10 mL of distilled water and continue to react for 0.5 h, then cool and filter to obtain a rare earth metal trifluoroacetate solution, continue to heat and evaporate at 80°C until trifluoroacetate compound crystals precipitate, dry to obtain a solid powder of trifluoroacetate of the corresponding rare earth element; slowly heat 20 mL of zirconium acetate solution with a concentration of 15% to 16% until zirconium acetate crystals precipitate on the surface of the solution, transfer to a 60°C oven for drying to obtain a solid zirconium acetate powder.

[0068] (2) Preparation of core nanocrystals Na3ZrF7:Yb,Er,Ce by high temperature solvothermal method: 0.2456 g zirconium acetate, 0.1024 g ytterbium trifluoroacetate, 0.0101 g erbium trifluoroacetate and 0.0145 g cerium trifluoroacetate were weighed in a reaction flask, and 10 mL oleic acid and 20 mL octadecene were added; the mixture was heated to 130 °C under stirring and vacuum state, and when no bubbles were generated, the vacuum device was closed and nitrogen was passed through for 30 min, then the temperature was raised to 156 °C and nitrogen was passed through for 30 min, and then the mixture was naturally heated to 156 °C. The reaction mixture was cooled to 40°C; 10 mL of a methanol solution containing 0.12 g of sodium hydroxide and 0.1852 g of ammonium fluoride was slowly added to the system and stirred for 30 min. The reaction system was heated to 130°C under stirring and vacuuming. When no more bubbles were generated, the vacuuming device was turned off and nitrogen was passed through for 30 min. The temperature was then raised to 250°C and maintained for 60 min. The system was then naturally cooled to room temperature to obtain core nanocrystals Na3ZrF7:Yb,Er,Ce. The structure of the core nanocrystals was characterized. The transmission electron microscope image is shown in FIG. Figure 1 shown.

[0069] (3) Preparation of core-shell nanocrystals Na3ZrF7:Yb,Er,Ce@CaF2:Yb,Tm,Zr by coating method: 0.4179gCa(CF3COO)2, 0.2048g ytterbium trifluoroacetate, 0.0051g thulium trifluoroacetate and 0.0065g zirconium acetate solid were added to the three-necked flask containing the core nanocrystals in step (2); heated to 130°C under stirring and vacuum state, and when no bubbles were generated, the vacuum device was turned off, nitrogen was passed through for 0.5h, and then the temperature was raised to 260°C for reaction for 1h, and then naturally cooled to room temperature.

[0070] (4) Preparation of core-shell-shell nanocrystals Na3ZrF7:Yb,Er,Ce@CaF2:Yb,Tm,Zr@CaF2:Zr by coating method: 0.2582g Ca(CF3COO)2 and 0.0098g zirconium acetate were added to the three-necked flask storing the core-shell nanocrystals in step (3), and the amounts of the two substances were the same; heated to 130°C under stirring and vacuum state, and when no bubbles were generated, the vacuum device was turned off, nitrogen was passed through for 0.5h, and then the temperature was raised to 270°C for reaction for 1h, and then naturally cooled to room temperature; after centrifugal washing with ethanol and cyclohexane, the prepared core-shell-shell nanocrystals were stored in cyclohexane liquid and their structure was characterized. The transmission electron microscope image is shown as follows: Figure 2 The results show that the core-shell-shell nanocrystals have uniform size and good dispersibility, which ensures their good luminescence performance, and because they are not easy to agglomerate, the core-shell-shell nanocrystals have good biosafety.

[0071] X-ray diffraction experiments were performed on the obtained core nanocrystals and core-shell-shell nanocrystals, and the results are as follows: Figure 3 As shown, the results show that each X-ray diffraction peak of the core nanocrystal and the core-shell-shell nanocrystal corresponds well to the XRD standard card of Na3ZrF7, proving that the core nanocrystal and the core-shell-shell nanocrystal have good crystallinity. Then the cyclohexane solution containing the core-shell-shell nanocrystal was mixed with PBS (pH=5.5). After 12 hours, the transmission electron microscope image of the core-shell-shell nanocrystal in the upper cyclohexane solution was as follows: Figure 4 As shown, the results show that the morphology of the core-shell-shell nanocrystals was significantly destroyed after contacting with PBS (pH=5.5) for 12 hours, proving that the core-shell-shell nanocrystals have good degradation performance. In addition, a 980nm laser was used to excite the core nanocrystals and core-shell-shell nanocrystals in Example 1, and the upconversion emission spectrum was obtained as shown in Figure 5 As shown, the corresponding upconversion luminescence photos of core-shell-shell nanocrystals under 980nm laser excitation are shown in Figure 6 The down-conversion emission spectrum is shown in Figure 7 As shown, the results show that: after coating with Tm 3+ After the addition of CaF2:Yb,Tm,Zr active shell and CaF2:Zr inert shell, the upconversion and downconversion intensities of core-shell-shell nanocrystals are significantly enhanced compared with core nanocrystals. In addition, Tm appears in the upconversion spectrum of core-shell-shell nanocrystals. 3+ The blue-violet upconversion (emission peaks are around 410 nm and 475 nm, respectively) is conducive to the realization of light-assisted Fenton reaction, which improves the potential of core-shell-shell nanocrystals in anti-tumor applications. And due to the presence of red and green upconversion fluorescence of erbium ions, the overall emission of the nanocrystals is white, and its color coordinates are as follows: Figure 8 shown.

[0072] Embodiment 2:

[0073] This embodiment provides a white and near-infrared dual-mode luminescent degradable nanocrystal, and the preparation method thereof comprises the following steps:

[0074] (1) Synthesizing trifluoroacetates and zirconium acetates of rare earth metal elements ytterbium, erbium, cerium and thulium respectively: at room temperature, take 30 mmol of oxides of rare earth metals ytterbium, erbium, cerium and thulium and 180 mmol of trifluoroacetic acid respectively and mix them evenly in a container, slowly heat the mixed solution to 80°C under stirring, add 15 mL of distilled water and continue to react for 1 hour, then cool and filter to obtain a rare earth metal trifluoroacetate solution, continue to heat and evaporate at 80°C until trifluoroacetate compound crystals precipitate, dry to obtain a solid powder of the trifluoroacetate of the corresponding rare earth element; slowly heat 30 mL of zirconium acetate solution with a concentration of 15% to 16% until zirconium acetate crystals precipitate on the surface of the solution, transfer to a 50°C oven for drying to obtain a solid zirconium acetate powder.

[0075] (2) Preparation of Na3ZrF7:Yb, Er, Ce core nanocrystals by high temperature solvothermal method: 0.2456 g zirconium acetate, 0.1024 g ytterbium trifluoroacetate, 0.0101 g erbium trifluoroacetate and 0.0145 g cerium trifluoroacetate were weighed into a reaction flask, 10 mL oleic acid and 20 mL octadecene were added; heated to 130 °C under stirring and vacuum state, and when no bubbles were generated, the vacuum device was closed, nitrogen was passed through for 35 min, and then the temperature was raised. To 156 ° C, pass nitrogen for 40 minutes, and then cool naturally to 40 ° C; 15 mL of methanol solution containing 0.12 g of sodium hydroxide and 0.1852 g of ammonium fluoride is slowly added to the above system and stirred for 40 minutes. The reaction system is heated to 130 ° C under stirring and vacuuming. When no bubbles are generated, the vacuuming device is turned off, nitrogen is passed for 30 minutes, and then the temperature is raised to 250 ° C and maintained for 60 minutes, and then naturally cooled to room temperature.

[0076] (3) Preparation of core-shell nanocrystals Na3ZrF7: 20% Yb, 2% Er, 3% Ce@CaF2: 20% Yb, 0.5% Tm, 1% Zr by coating method: 0.4179 g Ca(CF3COO)2, 0.2048 g ytterbium trifluoroacetate, 0.0051 g thulium trifluoroacetate and 0.0065 g zirconium acetate were added to the three-necked flask containing the core nanocrystals in step (2); heated to 130°C under stirring and vacuum state, and when no bubbles were generated, the vacuum device was turned off, nitrogen was passed through for 40 min, and then the temperature was raised to 260°C for reaction for 1 h, and then naturally cooled to room temperature.

[0077] (4) Core-shell-shell nanocrystals Na3ZrF7:20%Yb,2%Er,3%Ce@CaF2:20%Yb,0.5%Tm,1%Zr@CaF2:3%Zr were prepared by coating method. : Add 0.2582g Ca(CF3COO)2 and 0.0098g zirconium acetate to the three-necked flask storing the core-shell nanocrystals in step (3); heat to 130°C under stirring and vacuuming, and when no bubbles are generated, turn off the vacuuming device, pass nitrogen for 40min, then raise the temperature to 270°C for reaction for 1h, and then cool naturally to room temperature; after centrifugal washing with ethanol and cyclohexane, store the prepared core-shell-shell nanocrystals in cyclohexane liquid.

[0078] It should be noted that the present invention provides a white and near-infrared dual-mode luminescent degradable nanocrystal, the method used is simple and easy, the generated luminescent nanocrystal has good dispersibility, uniform particle size distribution, small particle size, and is green and environmentally friendly; the ytterbium ion in the core is used as a sensitizer to capture 980 nm photons, and due to the unique cross-relaxation effect between cerium and erbium, after ytterbium transfers energy to the activator erbium ion, the photons on the near-infrared second light energy level of erbium are rapidly accumulated, while the photons on the red and green light energy levels of erbium are sharply reduced, and when the cerium doping concentration is 3%, the near-infrared second emission is the strongest. The smaller core is conducive to increasing the probability of occurrence of such cross relaxation. The thulium ion with a concentration of 0.5% is doped in the first layer of CaF2 shell, giving the nanocrystal blue-violet upconversion, and due to the presence of red and green upconversion fluorescence of erbium ions, the overall luminescence of the nanocrystal is white. The outermost coated CaF2 shell can eliminate the fluorescence quenching of thulium ions and greatly improve the intensity of up-conversion white luminescence. The preparation method of the present invention has a simple and easy operation, uniform particle size distribution, high product purity, and is green and environmentally friendly. By doping with different rare earth elements and constructing a core-shell structure, the nanocrystals are given strong white and near-infrared fluorescence. The near-infrared fluorescence makes it a potential optical imaging contrast agent, and the white light emission makes the prepared nanocrystals can be used as a nano energy "converter" for light-triggered therapy. In addition, the biodegradability of the product of the present invention enables the rare earth up-conversion nanocrystals to be biodegraded into harmless products after playing the diagnostic and therapeutic functions in the body, and can be metabolized from the body, and the CaF2 shell has a regulating effect on the degradation rate of the nanocrystals. Therefore, the nanocrystal can be used as a potential integrated diagnosis and treatment nano-platform.

[0079] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A method for preparing white and near-infrared dual-mode luminescent degradable nanocrystals, characterized in that: The following steps are involved: S1, reacting oxides of rare earth metals ytterbium, erbium, cerium and thulium with a trifluoroacetic acid solution to obtain trifluoroacetates of rare earth metals ytterbium, erbium, cerium and thulium; S2, using the trifluoroacetates of rare earth metals ytterbium, erbium and cerium and zirconium acetate solids prepared in step S1 as raw materials, and adopting a high temperature solvothermal method to prepare core nanocrystals Na3ZrF7:Yb,Er,Ce; S3, adding trifluoroacetate of Ca(CF3COO)2, zirconium acetate, rare earth metals ytterbium and thulium to the core nanocrystals Na3ZrF7:Yb,Er,Ce obtained in step S2, and preparing core-shell nanocrystals Na3ZrF7:Yb,Er,Ce@CaF2:Yb,Tm,Zr by coating method; S4, Ca(CF3COO)2 and zirconium acetate were added to the core-shell nanocrystals Na3ZrF7:Yb,Er,Ce@CaF2:Yb,Tm,Zr, and the coating method was used again to prepare white and near-infrared dual-zone dual-mode luminescent biodegradable nanocrystals Na3ZrF7:Yb,Er,Ce@CaF2:Yb,Tm,Zr@CaF2:Zr with a core-shell-shell structure.

2. The method for preparing white and near-infrared dual-mode luminescent degradable nanocrystals according to claim 1, characterized in that: Step S1 specifically includes: At room temperature, 10 mmol to 30 mmol of oxides of rare earth metals ytterbium, erbium, cerium and thulium and 60 mmol to 180 mmol of trifluoroacetic acid are respectively taken in a container and mixed evenly, the mixed solution is slowly heated to 80°C under stirring, 10 mL to 20 mL of distilled water is added and the reaction is continued for 0.5 h to 1 h, then the solution is cooled and filtered to obtain a rare earth metal trifluoroacetate solution, and the solution is further heated and evaporated at 60°C to 100°C until trifluoroacetate compound crystals are precipitated, and then dried to obtain a solid powder which is the trifluoroacetate of the corresponding rare earth element.

3. The method for preparing white and near-infrared dual-mode luminescent degradable nanocrystals according to claim 1, characterized in that: The method further includes the following steps between step S1 and step S2: A zirconium acetate solution with a concentration of 15% to 16% is slowly heated until zirconium acetate crystals precipitate on the surface of the solution, and then transferred to an oven at 60°C to 80°C for drying to obtain solid zirconium acetate powder.

4. The method for preparing white and near-infrared dual-mode luminescent degradable nanocrystals according to claim 1, characterized in that: Step S2 mainly includes: Weigh 75% zirconium acetate, 20% ytterbium trifluoroacetate, 2% erbium trifluoroacetate and 3% cerium trifluoroacetate in molar fractions into a reaction flask, add oleic acid and octadecene in a volume ratio of 1:2 to form solution A; heat the solution A to 120°C to 140°C under vacuum, turn off the vacuum device when no bubbles are generated, pass nitrogen for 20min to 40min, then heat to 150°C to 160°C, keep for 20min to 40min, and then cool to 40~50°C for use; add 10~15mL of solution A to a flask ... A methanol solution containing 2 to 4 times the amount of sodium hydroxide and 3 to 6 times the amount of ammonium fluoride as the amount of a rare earth trifluoroacetate precursor is added to the solution A after the reaction and the stirring is continued for 30 to 45 minutes. The reaction system is then heated to 120 to 140° C. under stirring and vacuuming. When no bubbles are generated, the vacuum device is closed and nitrogen is passed through for 20 to 40 minutes. The temperature is then raised to 240 to 260° C. again and maintained for 40 to 60 minutes. The reaction system is then naturally cooled to room temperature to obtain core nanocrystals Na3ZrF7:Yb, Er, Ce.

5. The method for preparing white and near-infrared dual-mode luminescent degradable nanocrystals according to claim 1, characterized in that: Step S3 mainly includes: Calculated by the molar fraction, 79.5% Ca(CF3COO)2, 20% ytterbium trifluoroacetate, 0.5% thulium trifluoroacetate and 1% zirconium acetate were directly added to a reaction flask containing core nanocrystals Na3ZrF7:Yb,Er,Ce, and heated to 120-140°C under stirring and vacuum. When no bubbles were generated, the vacuum device was turned off, nitrogen was passed through for 0.5-1h, then the temperature was raised to 250-270°C for reaction for 1-1.5h, and then cooled to room temperature to obtain core-shell nanocrystals Na3ZrF7:Yb,Er,Ce@CaF2:Yb,Tm,Zr.

6. The method for preparing white and near-infrared dual-mode luminescent degradable nanocrystals according to claim 5, characterized in that: The ratio of the amount of the core nanocrystal to the sum of the amounts of Ca(CF3COO)2, ytterbium trifluoroacetate, thulium trifluoroacetate and zirconium acetate is 1:

2.

7. The method for preparing white and near-infrared dual-mode luminescent degradable nanocrystals according to claim 1, characterized in that: Step S4 mainly includes: According to the molar fraction, 97% Ca(CF3COO)2 and 3% zirconium acetate are directly added to a reaction flask containing core-shell nanocrystals Na3ZrF7:Yb,Er,Ce@CaF2:Yb,Tm,Zr; the mixture is heated to 120-140°C under stirring and vacuuming, and when no bubbles are generated, the vacuuming device is turned off, nitrogen is passed through and maintained for 0.5-1h, then the temperature is raised to 250-270°C for reaction for 1-1.5h, and the mixture is cooled to room temperature to obtain white and near-infrared dual-mode luminescent degradable nanocrystals Na3ZrF7:Yb,Er,Ce@CaF2:Yb,Tm,Zr@CaF2:Zr with a core-shell-shell structure.

8. The method for preparing white and near-infrared dual-mode luminescent degradable nanocrystals according to claim 7, characterized in that: The amount of the core-shell nanocrystals is the same as the sum of the amounts of Ca(CF3COO)2 and zirconium acetate.

9. A core-shell-shell structured white and near-infrared dual-mode luminescent degradable nanocrystal prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The chemical formula is: Na3ZrF7:Yb,Er,Ce@CaF2:Yb,Tm,Zr@CaF2:Zr.

10. Use of the white and near-infrared dual-mode luminescent degradable nanocrystals according to claim 9 in preparing biological imaging probes or drug carriers.

Citation Information

Patent Citations

  • Biodegradable up-conversion core-shell nanocrystal and preparation method and application thereof

    CN112940711A

  • In vivo degradable upconversion nanomaterial, and preparation method therefor and use thereof

    WO2021134786A1